Effects of resistance training on the mental health of patients with fibromyalgia: a systematic review - Andreato L.V.* (2021)
© 2021, International League of Associations for Rheumatology (ILAR).Fibromyalgia is a chronic disease characterized by generalized skeletal muscle pain and the presence of mental disorders is common among patients. As there is no cure, several treatment alternatives have been investigated, including the practice of resistance training. Thus, the aim of the current study is to analyze the effects of resistance training on the mental health of patients with fibromyalgia. This is a systematic review of the literature that followed the recommendations of the PRISMA statement. The search for articles occurred in May 2020 in the databases PubMed, Embase, Science Direct, Web of Science, PEDro, and CINAHL, as well as Google Scholar for gray literature. The protocol was recorded in PROSPERO and assessment of quality was performed using the Cochrane tool. In total, 481 studies were found in the database searches, of which seven were included in the analysis. The only variables investigated in studies related to mental health were depression and anxiety. The results demonstrate that resistance training reduces symptoms of depression and anxiety in patients with fibromyalgia. It is concluded that resistance training is efficient to improve the mental health of patients with fibromyalgia, reducing depression and anxiety. The main limitation is that few variables related to mental health were analyzed.Key Points• Resistance training improves the mental health of patients with FM.• The most commonly studied variables related to mental health are depression and anxiety.• The study protocols are similar, starting with low-intensity training and gradually increasing the intensity.